Broken beauty musical modernism and the representation of disability - Straus, Joseph Nathan 1954- (Oxford University Press, 2018)
'Broken beauty' draws on two decades of work in disability studies and a growing body of recent work that brings the discussion of disability into musicology and music theory
Previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Geschichte 1900-; People with disabilities in music; Music / 20th century / Philosophy and aesthetics; Modernism (Music); Moderne; Musik; Behinderung